Exploring the impact of teacher quality on student academic achievement in primary schools - Martin , Andre Anthony (American Journal of Social Sciences and Humanities, 2023)
There has been debate among scholars, policymakers, and practitioners regarding the effects of teacher quality on students' academic performance. This quantitative descriptive study seeks to determine the impact of teacher quality on students' performance and the relationship between teacher quality and student performance. Student performance was measured using regional assessments in mathematics and language arts. A survey was conducted to collect primary data from teachers, and both sets of data were analyzed using the t-test, ANOVA, and Pearson’s correlation coefficient (r) to test for performance differences and relationships between student performance and teacher quality. The findings revealed no significant differences in the academic performances among students taught by trained and untrained teachers, degree and non-degree teachers, and teachers with varying years of experience and hours of professional development. The interactions of the teacher quality variables had no practical effect on student performance, and there were no significant relationships between student performance and the teacher quality variables of experience and professional development. There are implications for reorganizing or advancing teacher professional development, training, certification and licensing. The study adds to the scarce literature in the region and can guide policy development in teacher workforce planning, retention, and hiring.